Whole‐Heart 4D Flow MRI for Evaluation of Normal and Regurgitant Valvular Flow: A Quantitative Comparison Between Pseudo‐Spiral Sampling and EPI Readout. Issue 4 (17th March 2022) - Blanken, Carmen P.S.; Gottwald, Lukas M.; Westenberg, Jos J.M.; Peper, Eva S.; Coolen, Bram F.; Strijkers, Gustav J.; Nederveen, Aart J.; Planken, R. Nils; van Ooij, Pim
Abstract : EPI And Proud 4D Flow MRI Streamline Visualizations of Blood Flow through the Aortic Valve (A, B, Orange), Pulmonary Valve (A, B, Blue), Mitral Valve (C, D, Orange), and Tricuspid Valve (C D, Blue) in A 31‐Year‐Old Healthy Subject, Resulting from Semiautomated Retrospective Valve Tracking. Measured Flow Volumes Across the Valves are Listed in the Figure. Valve Tracking was Performed on Bssfp Cine Images on Two Orthogonal Views for Each Heart Valve. Four‐Chamber BSSFP View is Visible in the Background. Visit www.ismrm.org or Call +1 510 841 1899 for Information on Becoming an ISMRM Corporate Member by Blanken et al. (1120‐1130)